Monomer and excimer emission in a conformational and stacking-adaptable molecular system - Shan, Xueru (2023)
A design strategy that combines molecular conformation, alkyl chain length, and charge-transfer effects has been developed to obtain conformational and stacking-adaptable donor-acceptor-π type molecules for precisely regulating the monomer and excimer emission in a single luminous platform under different environments. These fluorophores can exhibit bright monomer emissions when they are in the dispersed state based on their planar conformation. However, when the luminous molecules with short alkyl side chains are in the crystalline state, their molecular conformation can become distorted, further inducing strong intermolecular interactions and staggered π-π stacking for bright excimer emission. More importantly, their dispersed and aggregated states can be reversibly regulated in a phase-change fatty acid matrix, to achieve temperature-responsive fluorescence for temperature monitoring and advanced information encryption.